MODEL-BASED LEARNING APPROACH INTEGRATED WITH AUGMENTED REALITY FOR ENHANCING GRADE 10 STUDENTS’ MODEL-BUILDING SKILLS AND SCIENTIFIC CONCEPTIONS IN SOLUTION TOPIC: การจัดการเรียนรู้โดยใช้แบบจำลองเป็นฐานร่วมกับเทคโนโลยีเสมือนจริงที่ส่งเสริมทักษะการสร้างแบบจำลองและมโนทัศน์ เรื่อง สารละลาย ของนักเรียนชั้นมัธยมศึกษาปีที่ 4 - Suradsrong, Kanokphorn; Kijkuakul, Sirinapa (Journal of Education and Innovation, 2020)
This research aims to develop a way to implement the model-based learning approach integrated with Augmented Reality technology to enhance students’ model-building skills and scientific conceptions in the solution topic. Research design was the action research consisting of Plan, Action, Observe and Reflect, which had been continued in 3 cycles. The participants were 45 Grade 10 students. Research instruments included lesson plans, reflective journals, semi-structured observations, 3D model evaluation protocol, semi-structured interviews and scientific conception test. Data were analyzed by content analysis and critiqued data creditability with resource and method triangulations. Research results revealed that Model-based learning approach consist of 4 steps included 1) creation of the model, 2) expression of the model, 3) test of the model, and 4) evaluation of the model. Also, the Augmented Reality technology was proceeded in step 3 to support the students’ more concrete model-building skill. Furthermore, the students appeared to have development of model-building skills in high level, especially improving their model. Also the skills helped almost 80 percent of them to have scientific conceptions in the solution topic, especially the colligative properties of solution.